A study of production line operation in electronic manufacturing industry - Ong, Pei Shan (2014)
In this study, it discusses about evaluating and improving production system in electronic manufacturing industry by using simulation method. The scope of this study is focusing on the operation system of Functional Test jigs production line. The time frame covered is one year it is in the year of 2014. This study is conducted by using ARENA simulation software to simulate and model the production line. It is a quantitative study in which the performance is measured by the value added time, waiting time and productivity for the entire system of the Functional Test jigs production line. Results generated from the simulation show that adding a new holes drilling/milling workstation would produce signiﬁcant effect in reducing overall value added times and wait times and improving productivity